Mengenal Sistem Penentuan Posisi Global (GPS) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
Global Positioning System (GPS) is the navigation radio system and position determined using satellite. GPS is consisted of three main segments namely space segment, control system segment and user segment. Space segment consists of GPS satellite, control system includes monitoring stations and user segment consists of GPS user includes receiver devices, GPS signal as well as data processor. GPS is capqble in providing sevices to all kind os users in determining the precise position at any given time and locator anywhere on the surface of earth which high level of accuracy.